Hubungan mekanisme koping dengan perkembangan sosial emosional pada remaja di SMAN 1 Ngaglik Sleman Yogyakarta - Praptiwi Praptiwi; Sulistiyawati Sulistiyawati; Ngatini Ngatini (Caring : Jurnal Keperawatan, 2019)
Adolescence is a transition period from childhood towards adulthood that needs adjustment to the changes that happened in their life. Teenagers’ failure in their social & emotional development will result in their lack of sensitivity towards the environment and their ability in adapting among their friends. Thus, a tension will occur, and it will result in problem-solving behaviour (coping mechanism). This research attempts to figure out the relationship between the coping mechanism and adolescents’ social & emotional development in SMAN 1 Ngaglik, Sleman, Yogyakarta This research was carried out by using descriptive correlation approach and cross-sectional research design. The research population are class XI students of SMA N 1 Ngaglik, Sleman, Yogyakarta. There are 128 students taken as samples by applying random cluster sampling as the sample collection technique. The data were collected through the social and emotional development questionnaire and coping mechanism questionnaire. Then, the bivariate statistical test utilizes a chi-square test. The majority of the respondents are female with 89 female students (69.5%) as respondents. The coping mechanism under the emotion-focused coping category is 69.5%, and the social & emotional development is adequate, reaching 91.7%. According to the analysis of the correlation test, the p-value is 0.317. There is no relation between coping mechanism and the adolescents’ social & emotional development in SMAN 1 Ngaglik, Sleman, Yogyakarta